Did Photosymbiont Bleaching Lead to the Demise of Planktic Foraminifer Morozovella at the Early Eocene Climatic Optimum?. (6th November 2017) - Luciani, Valeria; D'Onofrio, Roberta; Dickens, Gerald R.; Wade, Bridget S.
Abstract: The symbiont‐bearing mixed‐layer planktic foraminiferal genera Morozovella and Acarinina were among the most important calcifiers of early Paleogene tropical–subtropical oceans. A marked and permanent switch in the abundance of these genera is known to have occurred at low‐latitude sites at the beginning of the Early Eocene Climatic Optimum (EECO), such that the relative abundance of Morozovella permanently and significantly decreased along with a progressive reduction in the number of species; concomitantly, the genus Acarinina almost doubled its abundance and diversified. Here we examine planktic foraminiferal assemblages and stable isotope compositions of their tests at Ocean Drilling Program Site 1051 (northwest Atlantic) to detail the timing of this biotic event, to document its details at the species level, and to test a potential cause: the loss of photosymbionts (bleaching). We also provide stable isotope measurements of bulk carbonate to refine the stratigraphy at Site 1051 and to determine when changes in Morozovella species composition and their test size occurred. We demonstrate that the switch in Morozovella and Acarinina abundance occurred rapidly and in coincidence with a negative carbon isotope excursion known as the J event (~53 Ma), which marks the start of the EECO. We provide evidence of photosymbiont loss after the J event from a size‐restricted δ 13 C analysis. However, such inferred bleaching was transitory and also occurred in the acarininids. The geologically rapid switch in planktic foraminiferal genera during the early Eocene was a major evolutionary change within marine biota, but loss of photosymbionts was not the primary causal mechanism. Key Points: The relative abundance of the Morozovella genus permanently decreased significantly at the J carbon isotope excursion (~53 Ma) Changes in bulk sediment stable isotopes correlate with changes in the abundance, composition, and size of the Morozovella species Photosymbiont inhibition was probably not the primary cause of the remarkable Morozovella decline Plain Language Summary: The planktic foraminiferal genera Morozovella and Acarinina were among the most important calcifiers of early Paleogene tropical‐subtropical oceans. A marked and permanent switch in the abundance of these genera occurred at low‐latitude sites at the beginning of the Early Eocene Climatic Optimum (ca 49‐53 Ma), the time interval when Earth temperatures and atmospheric carbon dioxide pressure reached their maximum of the last 100 Ma. Here we examine in detail changes in planktic foraminiferal assemblages and their geochemistry at Ocean Drilling Program Site 1051 (northwest Atlantic). We test also a potential cause for the striking and permanent Morozovella decline in abundance and diversity: the loss of algal photosymbionts (bleaching). The switch in Morozovella and Acarinina abundance occurred rapidly across a negative carbon isotope excursion known as the J event, which marks the start of the Early Eocene Climatic Optimum. We show evidence of photosymbiont loss in morozovellids and a significant reduction of morozovellid test‐size after the J event. However, the recorded bleaching was a transitory effect and also involved the acarininids. The sudden switch in planktic foraminiferal genera during the early Eocene was a significant evolutionary change in the marine biota, but loss of photosymbionts was not the primary causal mechanism.